2017
DOI: 10.17925/usor.2017.10.01.57
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anti-vascular Endothelial Growth Factor Agents in the Management of Retinopathy of Prematurity

Abstract: Retinopathy of prematurity is a vasoproliferative disease of preterm infants and has effects on infant vision and overall development. It is increasing worldwide with advances in perinatal care. In the following manuscript, we review the pathophysiology and possible treatments. We focused on anti-vascular endothelial growth factor (VEGF) agents and a few select other candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…This study showed fewer re‐treatments in the bevacizumab group, but this was isolated to infants with ROP in zone 1 5. These agents inhibit VEGF which is an important growth factor in angiogenesis 6…”
mentioning
confidence: 83%
“…This study showed fewer re‐treatments in the bevacizumab group, but this was isolated to infants with ROP in zone 1 5. These agents inhibit VEGF which is an important growth factor in angiogenesis 6…”
mentioning
confidence: 83%
“…Dysregulation of VEGF is considered one of the underlying mechanisms for ROP [14]. Injection of anti-VEGF agents like Ranibizumab, Bevacizumab, and Aflibercept into the vitreous is a popular strategy for management of diseases associated with vaso-proliferation and hyperpermeability in adult ophthalmologic practices [3].…”
Section: Introductionmentioning
confidence: 99%